FENOMENA PENURUNAN ANGKA PERNIKAHAN DAN PERKEMBANGAN BUDAYA OMIAI DI JEPANG - Budi Mulyadi (KIRYOKU, 2018)
This paper entitled The Phenomenon of Decline in Marriage rates And Matchmaking Culture Development. The main goal of this article is to know the phenomenon of decline in marriage rates and matchmaking culture development in Japan.This reserach uses field research. Main methode are observation and interpretation.This paper shows that one of the factor behind the marriage rtaes decline in Japan is the relatively new-found "freedom" that young Japanese have, as a result of decreasing social pressure to settle down and start a family. Japan has also seen a shift in attitudes among the sexes, with young women increasingly seen as career-orientated and putting their own desires ahead of the need for a family. Men, on the other hand, have become more willing to put up with unhappiness in their careers merely to hang on to their jobs as well as being less domineering toward women.This paper also shows that there are development in Japanese mindset about matchmaking culture which take effect to decline in marriage rates in Japan.Keywords: matchmaking, marriage, Japanese culture.